ANALISIS PROGRAM PENGUATAN PENDIDIKAN KARAKTER PADA DINAS PENDIDIKAN KOTA BINJAI (IMPLEMENTASI DI SEKOLAH DASAR NEGERI RINTISAN PENDIDIKAN KARAKTER) - Evi Octoviyanti Siregar; Sri Nurabdiah Pratiwi; Salim Aktar (JGK (Jurnal Guru Kita), 2022)
Abstract: Analysis of the Character Education Strengthening Program at the Binjai City Education Office (Implementation in Character Education Pilot Elementary Schools). This study aims to find out how the strengthening of character education carried out by the Binjai City Education Office at the State Elementary School pioneering character education, and to find out whether the implementation of strengthening character education in the State Elementary School is an Effective Pilot. This research is a mixed qualitative and quantitative research with embedded methods. This research was conducted at the Binjai Education Office Jl. Mount Merapi No.1, Binjai Estate, South Binjai, Binjai City, North Sumatra. The data sources for this study were 2 (two) UPTDs, 1 (one) school supervisor, 3 (three) principals, and 30 (thirty) teachers. Interviews, questionnaires, observations, and documentation were used as data collection instruments. The findings of this study are the implementation of character education programs at the basic education unit level in the city of Binjai has been carried out in coordination, coordination is carried out through (1) meetings and (2) meetings. The Education Office's support in implementing character education includes; (1) make a written circular to the UPTD regarding the character education policy; (2) provide socialization to schools, both with the budget of the Binjai city government itself and as implementers of the central government program; (3) attending the school curriculum public test to see to what extent character education has been included in the school curriculum; and (4) assistance to schools, although not specifically for character education but improving the quality of schools in general, (5) providing training even though it is still considered not optimal. Support for facilities and infrastructure provided by the Department of Education for the implementation of character education in schools, among others, is to provide support for learning facilities and curriculum guidelines. Meanwhile, support for facilities and infrastructure available at schools such as worship facilities, places for finding lost items, honesty canteens, school rules, attendance records, display of pearls of wisdom, communication and information media, libraries, and cleaning facilities. The Education Office has provided assistance to the implementation of character education programs, such as technical assistance in the implementation and implementation of an integrated character education curriculum. The evaluation and assessment of the implementation of character education is carried out in an integrated manner, namely the education office through school supervisors, school principals, teachers and parents of students. The results of the implementation of the policy performance evaluation are reported to both the education office through the school supervisor and the students' parents. The implementation of the character education strengthening program has been effective. The research findings show that 92.5% of respondents strongly agree. This means that the implementation of the character education strengthening program by the Education Office is considered effective, 5.5% of respondents said it was effective, while 1% of respondents said it was not yet effective. Keywords: Strengthening Character Education Abstrak: Analisis Program Penguatan Pendidikan Karakter Pada Dinas Pendidikan Kota Binjai (Implementasi Di Sekolah Dasar Negeri Rintisan Pendidikan Karakter)Penelitian ini bertujuan untuk mengetahui bagaimana penguatan pendidikan karakter yang dilakukan Dinas Pendidikan Kota Binjai pada Sekolah Dasar Negeri rintisan pendidikan karakter, dan untuk mengetahui apakah implementasi penguatan pendidikan karakter di Sekolah Dasar Negeri Rintisan Efektif. Penelitian ini merupakan penelitian kualitatif dan kuantitatif bersifat campuran dengan metode embedded. Penelitian ini dilakukan di Dinas Pendidikan Binjai  Jl. Gunung Merapi No.1, Binjai Estate, Binjai Selatan, Kota Binjai, Sumatera Utara. Sumber data penelitian ini adalah 2 (dua) orang UPTD, 1 (satu) orang pengawas sekolah, 3 (tiga) orang kepala sekolah, dan 30 (tiga puluh) guru. Wawancara, angket, observasi, dan dokumentsi digunakan sebagai instrument pengumpulan data. Temuan penelitian ini adalah implementasi program pendidikan karakter di tingkat satuan pendidikan dasar di kota Binjai telah dilaksanakan kordinasi, kordinasi yang dilakukan melalui (1) pertemuan dan (2) rapat-rapat. Dukungan Dinas Pendidikan dalam pelaksanaan implementasi pendidikan karakter meliputi; (1) membuat edaran tertulis kepada UPTD mengenai kebijakan pendidikan karakter; (2) memberikan sosialisasi pada sekolah-sekolah, baik dengan anggaran pemerintah kota Binjai sendiri maupun sebagai pelaksana program pemerintah pusat; (3) hadir dalam uji publik kurikulum sekolah untuk melihat sampai sejauh mana itu pendidikan karakter sudah termuat dalam kurikulum sekolah; dan (4) pendampingan ke sekolah, meskipun tidak secara khusus untuk pendidikan karakter tetapi peningkatan mutu sekolah secara umum, (5) memberikan pelatihan meskipun masih dinilai belum maksimal. Dukungan sarana dan prasarana yang diberikan Dinas Pendidikan bagi pelaksanaan pendidikan karakter di sekolah antara lain yakni memberikan dukungan sarana belajar dan pedoman kurikulum. Sedangkan dukungan sarana dan prasarana yang tersedia disekolah seperti fasilitas ibadah, tempat temuan barang hilang, kantin kejujuran, tata tertib sekolah, catatan kehadiran, pajangan kata mutiara, media komunikasi dan informasi, perpustakaan, dan sarana kebersihan. Dinas Pendidikan telah memberikan pendampingan terhadap penyelenggaraan program pendidikan karakter, seperti pendampingan teknis pelaksanaan dan implementasi kurikulum yang terintegrasi pendidikan karakter. Pelaksanaan evaluasi dan penilaian terhadap implementasi pendidikan karakter dilakukan secara terpadu, yakni dinas pendidikan melalui pengawas sekolah, Kepala sekolah, guru dan orang tua siswa. Hasil pelaksanaan evaluasi kinerja kebijakan dilaporan baik kepada dinas pendidikan melalui pengawas sekolah maupun para orang tua siswa. Pelaksanaakn program penguatan pendidikan karakter telah efektif. Temuan penelitian menunjukkan 92,5% responden menyatakan sangat setuju. Ini berarti pelaksanaan program penguatan pendidikan karakter oleh Dinas Pendidikan di nilai sudah efektif, 5,5% responden menyatakan efektif, sedangkan sebanyak 1% responden menyatakan belum efektif. Kata kunci : Penguatan Pendidikan Karakter